Genotypic variation in biological nitrogen fixation by common bean - Hardarson, G.; Bliss, Fredrick A.; Cigales-Rivero, MR; Henson, R.A.; Kipe-Nolt, Judith A.; Longeri, L; Manrique, A; Pena-Cabriales, JJ; Pereira, Pedro Antônio Arraes; Sanabria, C.A.; Tsai, Siu Mui (Springer, 1993)
Field experiments were performed in Austria, Brazil, Chile, Colombia, Guatemala, Mexico and Peru as part of an FAO/IAEA Co-ordinated Research Programme to investigate the nitrogen fixing potential of cultivars and breeding lines of common bean (Phaseolus vulgaris L.). Each experiment included approximately 20 bean genotypes which were compared using the 15N isotope dilution method. Great differences in nitrogen fixation were observed between and within experiments, with average values of 35% N derived from atmosphere (% Ndfa) and highest values of 70% Ndfa being observed. These values which were larger than had been reported previously for common bean, were observed only when environmental factors were favorable. Therefore, common bean lines are available, which can support high biological nitrogen fixation. These can be used either directly as cultivars for production or in breeding programmes to enhance nitrogen fixation in other cultivars.